2017
DOI: 10.3390/en10091301
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulating Long-Timescale Cascading Faults in Power Systems Caused by Line-Galloping Events

Abstract: Abstract:With the increasing occurrence of extreme weather events, the short circuit and line-breaking faults in transmission lines caused by line galloping have been threatening the security operation of power systems. These faults are also hard to be simulated with current simulation tools. A numerical simulation approach of power systems is presented to simulate the clustered, cascading faults of long-timescale caused by line-galloping events. A simulation framework is constructed in which large numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The consideration of dynamic processes is essential and effective in the research on power systems in extreme weather. In [29] and [30], this idea was applied to the simulation of a power system considering the effects of icing and line galloping. However, the insulator flashover was ignored.…”
Section: Introductionmentioning
confidence: 99%
“…The consideration of dynamic processes is essential and effective in the research on power systems in extreme weather. In [29] and [30], this idea was applied to the simulation of a power system considering the effects of icing and line galloping. However, the insulator flashover was ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Galloping is a well-known phenomenon for iced electricity transmission lines. Galloping of multi-span conductors can reach high amplitude causing high tension on conductors, and the periodic change of the tension can be leaded to damage of sub-conductors, spacers, and towers (Kermani et al, 2013;Chen et al, 2017), which usually give rise to disruption of power supply, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Conductor galloping is caused by icing or strong winds and represents a major hazard, which may lead to various damages such as wire fractures or tower collapses and large-scale grid breakdowns. Hence, galloping prevention is imperative [1], [2].…”
Section: Introductionmentioning
confidence: 99%